Tindak Tutur Tak Langsung Dalam Surat Al-Kahfi (Kajian Analisis Pragmatik) - Kholid Akhmad Muzakki; Ahmad Rizza Firdaus; Annisa’ Fatmayanti (Nazhruna: Jurnal Pendidikan Islam, 2018)
Sentences by mode can be divided into three: sentence (declarative), interrogative, and command (imperative) sentences. Conventionally, declarative sentences are used if the speaker wants to declare or convey information to his or her opponent. Interrogative sentence is the sentence used if the speaker wants to get the information, the reaction or the expected answer. As for the imperative sentence, is if the speaker wants to enjoin or forbid his opponent to do something. But in pragmatic studies, there are times when the sentence is used non-conventionally. Declarative sentences, in addition to functioning to deliver the news, also enabled to ask; interrogative sentences other than enabled to ask is also enabled for the request or command. Meanwhile, the command line can only be used conventionally, and can not be used non-conventionally. When all three sentences are conventionally functioned, the speech is called direct speech act, whereas when used in a non-conventional way, it is called indirect speech act. The use of sentences indirectly has a purpose, among others, in order to maintain politeness. A command that explanation by using the sentence news or sentence, will be felt by the opponent said lighter, even for the opponent said the command on him is not perceived as a command. In the Qur'an there are many unusually functional sentences, indicating that the Qur'an is a holy book that strongly upholds language-based pride. One of them is Surah Al-Kahfi. In the Surah Al-Kahfi, found some verses which are indirect speech. In Surah Al-Kahfi, the forms of indirect speech are as follows. First, Declarative texts mean imperative is found in verse 16, 45, 52, 60 and 78. Second, Interrogative texts mean imperative is found in verse 6, 9 and 50. Third, Interrogative texts mean declarative is found in verses 15, 37, 57, 68, 75, 102 and 103.